Quality of life in patients with chronic kidney disease - Cruz, Maria Carolina (2011)
AIM: To compare the dimensions of quality of life in the stages of chronic kidney disease and the influence of sociodemographic, clinical and laboratory data. INTRODUCTION: The information available on the quality of life of patients on conservative treatment and the relationship between the quality of life and glomerular filtration rate is limited. METHODS: 155 patients in stages 1-5 of chronic kidney disease and 36 in hemodialysis were studied. Quality of life was rated by the Medical Outcomes Study Short Form 36-Item (SF-36) and functional status by the Karnofsky Performance Scale. Clinical, laboratory and sociodemographic variables were investigated. RESULTS: Quality of life decreased in all stages of kidney disease. A reduction in physical functioning, physical role functioning and in the physical component summary was observed progressively in the different stages of kidney disease. Individuals with higher educational level who were professionally active displayed higher physical component summary values, whereas men and those with a higher income presented better mental component summary values. Older patients performed worse on the physical component summary and better on the mental component summary. Hemoglobin levels correlated with higher physical component summary values and the Karnofsky scale. Three or more comorbidities had an impact on the physical dimension. CONCLUSION: Quality of life is decreased in renal patients in the early stages of disease. No association was detected between the stages of the disease and the quality of life. It was possible to establish sociodemographic, clinical and laboratory risk factors for a worse quality of life in this population.